Pengaruh Konsumsi Kurma Ajwa (Phoenix Dactylifera) Terhadap Kadar Hemoglobin Ibu Hamil Anemia - Fadhila, Umi Tanzil; Royani, Ida; Murfat, Zulfitriani; Mappaware, Nasrudin Andi; Khalid, Nurfadhilah (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Anemia is one of the indirect causes of death for pregnant women. In pregnant women, anemia is a condition in which red blood cells or hemoglobin levels in the blood decrease, so that the oxygen-carrying capacity for the needs of vital organs in the mother and fetus is reduced. Fruits that can increase hemoglobin levels of pregnant women are fruits that are rich in iron, one of which is dates. Islam is a religion that also provides a solution, namely by consuming ajwa dates. The purpose of this study is to determine the effect of giving ajwa dates on hemoglobin levels of anemic pregnant women. This study used a non-experimental design with the Narrative Review method. Literature searches are carried out through national journals, international journals, clinical keys, textbooks, and proceeding books. From the literature it was found that there was an increase in hemoglobin levels of pregnant women after consuming ajwa dates. This is because Ajwa dates are rich in iron and also contain various vitamins such as riboflavin, biotin, thiamine, folic acid and ascorbic acid which are important for the body. Based on the results of the literature review, it can be concluded that giving ajwa dates (Phoenix dactylifera) has an effect on increasing hemoglobin levels in pregnant women. Keywords : Dates, Ajwa Dates (Phoenix dactylifera), Anemia, Pregnant Women, Hemoglobin Levels  ABSTRAK Anemia merupakan salah satu faktor penyebab tidak langsung kematian ibu hamil. Pada ibu hamil, anemia merupakan kondisi sel darah merah atau kadar hemoglobin dalam darah menurun, sehingga kapasitas daya angkut oksigen untuk kebutuhan organ-organ vital pada ibu dan janin menjadi berkurang. Buah yang dapat meningkatkan kadar hemoglobin ibu hamil adalah buah yang kaya akan zat besi, salah satunya kurma. Agama Islam adalah agama yang turut memberikan solusi, yakni dengan mengonsumsi buah kurma ajwa. Tujuan penelitian ini yaitu untuk mengetahui pengaruh pemberian buah kurma ajwa terhadap kadar hemoglobin ibu hamil anemia. Penelitian ini menggunakan desain non-eksperimental dengan metode Narrative Review. Penelusuran pustaka dilakukan melalui jurnal nasional, jurnal internasional, clinical key, textbook, dan proceeding book. Dari literatur yang didapatkan bahwa terjadi peningkatan kadar hemoglobin ibu hamil sesudah kurma ajwa dikonsumsi. Hal ini dikarenakan kurma ajwa kaya akan zat besi dan juga mengandung berbagai vitamin seperti riboflavin, biotin, tiamin, asam folik, dan asam askorbat yang penting bagi tubuh. Berdasarkan hasil literature review dapat disimpulkan bahwa pemberian kurma ajwa (Phoenix dactylifera) memberikan efek terhadap peningkatan kadar hemoglobin ibu hamil. Kata Kunci: Kurma, Kurma Ajwa (Phoenix Dactylifera), Anemia, Ibu Hamil, Kadar Hemoglobin